Did Secularization among Peasants in the Kingdom of Poland Accelerate in the Period 1906–1912? Peasants, Anticlericalism, and Religious Discourse under the Late Russian Imperial Regime - Łukasz Kożuchowski (Zeitschrift für Ostmitteleuropa-Forschung)
The Kingdom of Poland and its Catholic Church were in trouble in the last years of Russian imperial rule. Three of the Church’s major problems, the Mariavites, the anticlerical weekly Zaranie, and the Macoch affair in the Jasna Góra sanctuary, are objects of deliberation in this article. These calamities accelerated a widescale process of secularization in the rural peasant population of Russian Poland. Questions are posed regarding the role of Russian imperial rule in the Kingdom in launching this secularization process. Other factors, such as rising levels of literacy and reading habits, could also have played a role. The text concentrates on the peasantry as the largest social group in the Kingdom, referencing ego documents (letters and memoirs) written by members of this social stratum as primary sources.